The Survival of Small Societies - Hawthorn, H.B. (Anthropologica, 2022)
The relative size and power of societies are variables that enter into the determination of the nature and extent of cultural change. Societies of relatively small size are likely to experience a greater cultural flow. Short of constructing indices of cultural gain and loss it can be said impressionistically that for societies of the Indian reserve type this flow is likely to result in net cultural loss, as the loci of control, creativity and decision are removed from them. However, where separate identity becomes valued for its own sake, or where specific institutions are valued highly, even small societies are able to halt or reverse this process.